2010
DOI: 10.1007/s11368-009-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

A rapid spectral-reflectance-based fingerprinting approach for documenting suspended sediment sources during storm runoff events

Abstract: Purpose This paper reports on the development of a rapid and simple spectra-reflectance-based fingerprinting approach for documenting suspended sediment sources during storm runoff events. The methodology was applied in the rural Wollefsbach catchment (4.4 km 2 , NW Luxembourg). Materials and methods Different chemical properties of the sediment retained on glass fibre filters after filtration were predicted from VIS/NIR spectra (ASD FieldSpec-II spectrometer, 0.4-2.5 µm) through partial least-square regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 54 publications
2
48
0
Order By: Relevance
“…The findings show that the initially readily-available material from cultivated topsoil becomes supply-limited. The authors attribute the limited supply to the presence of artificial drains on the edges of the arable fields which disconnect the cultivated topsoils from the river network (Martínez-Carreras et al, 2010). A recent fingerprinting study by Cooper et al (2014a) defined sediment sources by erosion processes (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings show that the initially readily-available material from cultivated topsoil becomes supply-limited. The authors attribute the limited supply to the presence of artificial drains on the edges of the arable fields which disconnect the cultivated topsoils from the river network (Martínez-Carreras et al, 2010). A recent fingerprinting study by Cooper et al (2014a) defined sediment sources by erosion processes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have demonstrated the promise of spectral reflectance-based (visible and (near) infrared) fingerprinting methods as a quicker and less costly alternative for sediment source apportionment, with considerable potential to expand the temporal resolution of sediment fingerprinting analyses during high-flow events (e.g. Cooper et al, 2014aCooper et al, , 2014bEvrard et al, 2013;Martínez-Carreras et al, 2010;Poulenard et al, 2009;Tiecher et al, 2015).…”
Section: Methodological Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have previously used NIR spectroscopy to assess the physical and chemical properties of catchment source materials by linking the spectra with regression models for predicting mineralogical and organic matter (e.g. Hillier, 2001;Poulenard et al, 2009Poulenard et al, , 2012 or geochemical constituents (Elliott et al, 2007;Martínez-Carreras et al, 2010). In this study, however, the absorbance values of the peaks in the NIR spectra were used to provide fingerprints thereby avoiding the need to develop predictive regression models for specific constituents of particulate matter (cf.…”
Section: Propertymentioning
confidence: 99%
“…In addition, it would be desirable to have integral measures of hydrological behaviour, such as sediment fingerprinting (Martínez-Carreras et al 2010) to characterize the source area of overland flow, or distributed soil moisture data (Brocca et al 2007, Zehe et al 2010 to verify the simulated soil moisture dynamics against either distributed point data or spatially clustered data. Further, use of a larger number of reference catenas would be advantageous.…”
Section: Discussionmentioning
confidence: 99%